Activation of smooth muscle BK channels by hydrochlorothiazide requires cell integrity and the presence of BK β1-subunits - Martín, Pedro (2017)
Thiazide-like diuretics are one of the most commonly used drugs to treat arterial hypertension, with their efficacy being linked to their chronic vasodilatory effects. Previous studies have suggested that activation of the large conductance voltage- and Ca2+-dependent K+ (BK) channel (Slo 1, MaxiK channel) is responsible for the thiazide-induced vasodilatory effect. However, direct electrophysiological evidence supporting this claim is lacking. BK channels can be associated with small accessory β-subunits (β1-β4) that confer specific biophysical and pharmacological characteristics to the current phenotype. The β1-subunit is primarily expressed in smooth muscle cells (SMCs). The effect of hydrochlorothiazide (HCTZ) on BK channel activity was measured using patch-clamp electrophysiology on native SMCs from human umbilical artery (HUASMCs) and HEK293T cells expressing the BK channel (with and without the β1-subunit). HCTZ significantly activated the BK current when evaluated using the whole-cell and cell-attached configurations. However, HCTZ did not affect the unitary conductance and open probability of the BK channel in the inside-out configuration, suggesting an indirect mechanism requiring cell integrity. The increase in BK channel activity due to HCTZ was concentration dependent, with an EC50 of 28 μmol/L, and membrane potential did not influence the concentration relationship. Moreover, our data c learly demonstrated that the HCTZ-induced activation of BK channels required the presence of β1-subunits. A β1-subunit-dependent mechanism that requires SMC integrity leads to HCTZ-induced BK channel activation.